Software Process Quality- Management and Control - S. Kenett, Ron (CRC Press, 2009)
Software presents both an opportunity and a threat. Software runs our lives. The list of applications in which software is a critical component is endless: elevators, airlines, telecommunications, medical devices, education, and countless others. Data from the Software Engineering Institute indicates that approximately 60% of software development organizations that have had formal assessments designed to determine how their software is developed are at the lowest level of capability. These assessments are based on the Capability Maturity Model—a framework for achieving process improvement. This lowest level is characterized as ad hoc and chaotic, having virtually nothing in the way of organized project management or software engineering practices. Over 600 organizations worldwide have gone through such assessments. These are organizations that have either embarked on improvement efforts of their software development process or made a commitment to do so. If we add in all the organizations that have not had assessments performed, or have no plans to implement process improvement, we estimate that the number of organizations at the lowest level is probably well in excess of 80%.